MAE414 : Fundamental of data management for primary school teachers / Faculty of Education - UiTM, Faculty of Education (Universiti Teknologi MARA (UiTM), 2023)
This course discusses the mathematical content in the area of statistics which covers the topics of average and data representation. It provides an introduction to the fundamental methods of data management in tabulation, graph production and descriptive statistics. This includes introduction to different types of data (measurement scales), and ways to present data (tables and graphs). This will be followed by the introduction to different frequency distributions and descriptive statistics, including mean, mode, median and measures of variance (standard deviation). The focus will be on both concepts and numbers computations with greater emphasis on the former. Students will also examine knowledge of children’s thinking and learning of the above topics. The development of pedagogical content knowledge for certain topics will be discussed in detail.